A possibilidade de um método de interpretação para o direito: uma análise a partir da hermenêutica filosófica - Isaac Maynart Carvalho Moyses Souza (2023)
The present dissertation has as object of study hermeneutics and the interpretation of Law. The main objective of the research is to investigate the possibility or viability of a method of interpreting the Law that serves to indicate a singular result in accordance with the Law itself or with what is called here the justice of the positive Law. In order to achieve the objective, a path was taken through the bibliographic review technique and from the philosophical hermeneutics of Hans-Georg Gadamer (in particular, what he developed in Truth and Method I) as the main theoretical reference. Finally, it was concluded, from the theoretical perspective adopted here, that there is no possibility of creating this method.